2017
DOI: 10.3892/etm.2017.4512
|View full text |Cite
|
Sign up to set email alerts
|

Induction of reprogramming of human amniotic epithelial cells into iPS cells by overexpression of Yap, Oct4, and Sox2 through the activation of the Hippo-Yap pathway

Abstract: The present study has reported a novel method for producing induced pluripotent stem (iPS) cells. Primary human amniotic epithelial cells (HuAECs) were isolated from the amniotic membranes of pregnant women who received Cesarean sections. These cells were infected with retroviruses carrying octamer-binding transcription factor 4 (Oct4), (sex determining region Y)-box 2 (Sox2) and Yes-associated protein (Yap) (OSY). Following in vitro culture for ~14 days, epithelial-like HuAECs exhibited several iPS clone-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The role of YAP in controlling pluripotency is seen in induced pluripotent stem cells (iPSCs), which was established by using the ectopic expression of Oct3/4, Sox2, Klf4 , and c-Myc genes closely resemble that of ESCs in phenotype and differentiation potential (124, 134). YAP is activated during the reprogramming process of human embryonic fibroblasts into iPSCs, and the addition of YAP to original four factors increases the reprogramming efficiency in mouse embryonic fibroblasts, further confirming a positive role of YAP in stemness (135). As in human ESCs, the interaction between YAP and TEADs directs transcriptional circumstances important for maintaining pluripotency.…”
Section: Hippo Pathway In Early Embryonic Development Stemness Maintmentioning
confidence: 73%
See 1 more Smart Citation
“…The role of YAP in controlling pluripotency is seen in induced pluripotent stem cells (iPSCs), which was established by using the ectopic expression of Oct3/4, Sox2, Klf4 , and c-Myc genes closely resemble that of ESCs in phenotype and differentiation potential (124, 134). YAP is activated during the reprogramming process of human embryonic fibroblasts into iPSCs, and the addition of YAP to original four factors increases the reprogramming efficiency in mouse embryonic fibroblasts, further confirming a positive role of YAP in stemness (135). As in human ESCs, the interaction between YAP and TEADs directs transcriptional circumstances important for maintaining pluripotency.…”
Section: Hippo Pathway In Early Embryonic Development Stemness Maintmentioning
confidence: 73%
“…In human iPSC, knockdown of LATS2 increases the reprogramming efficiency of iPSCs (136). Moreover, a recent study reported the success in reprograming of iPSCs derived from primary human amniotic epithelial cells (HuAECs) through the introduction of OSY ( OCT3/4, SOX2 , and YAP ) to activate the Hippo-Yap signaling pathway (135).…”
Section: Hippo Pathway In Early Embryonic Development Stemness Maintmentioning
confidence: 99%
“…Perhaps the most compelling evidence of the role of YAP/TAZ in the self-renewal and pluripotency of human pluripotent stem cells comes from studies on reprogramming adult somatic cells into iPSCs. Zhao et al (2017) reported that when YAP is ectopically expressed, only two reprogramming factors -Oct4 and Sox2 -instead of the usual four reprogramming factors (Oct4, Sox2, c-Myc and Klf4) are required to reprogram human amniotic epithelial cells into iPSCs. Qin et al (2012) showed that knockdown of LATS2, a key component of the Hippo pathway involved in the phosphorylation of YAP, which facilitates its retention within the cytosol, could increase the efficiency of reprogramming of human somatic cells into iPSCs.…”
Section: Role Of Yap/taz In Stem Cell Self-renewal and Maintenance Ofmentioning
confidence: 99%
“…miRNAs have no open reading frame and do not encode a protein product with a specific function, but as single-stranded ncRNAs, they can reverse-complement with the mRNA transcripts of other genes to silence the target genes after transcription. In addition, YAP plays an important role in cell division and differentiation, stem cell fate decisions, and tumorigenesis and progression (Zhao et al, 2011;Xie et al, 2012;He et al, 2017;Li et al, 2017;Xiao et al, 2017;Zhang et al, 2017;Zhao et al, 2017;Zhuo and Kang, 2017). The Hippo-YAP/TAZ (Yesassociated protein/YLP motif-containing 1) pathway is a kinase cascade consisting of a series of protein kinases and transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of nuclear YAP blocks Hippo-YAP/TAZ pathway activity and inhibits further cell and tissue growth (Xie et al, 2012;Cabochette et al, 2015). In addition, YAP plays an important role in cell division and differentiation, stem cell fate decisions, and tumorigenesis and progression (Zhao et al, 2011;Xie et al, 2012;He et al, 2017;Li et al, 2017;Xiao et al, 2017;Zhang et al, 2017;Zhao et al, 2017;Zhuo and Kang, 2017). Recently, an increasing number of studies have shown that Hippo-YAP/TAZ signaling has emerged as a new pathway for blood vessel development (Park and Kwon, 2018).…”
Section: Introductionmentioning
confidence: 99%